2002
DOI: 10.1182/blood.v99.8.2851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous interleukin-7 on human thymus function

Abstract: Immune reconstitution is a critical component of recovery after treatment of human immunodeficiency virus (HIV) infection, cancer chemotherapy, and hematopoietic stem cell transplantation. The ability to enhance T-cell production would benefit such treatment. We examined the effects of exogenous interleukin-7 (IL-7) on apoptosis, proliferation, and the generation of T-cell receptor rearrangement excision circles (TRECs) in human thymus. Quantitative polymerase chain reaction demonstrated that the highest level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 68 publications
6
77
2
Order By: Relevance
“…Notably, they include early thymocyte progenitors, including CD34 ϩ subpopulations, as well as more mature SP thymocytes. These results confirm previously published data from Okamoto et al (17), who showed that IL-7 treatment of human TOCs led to decreased apoptosis and increased intracellular Bcl-2 levels in immature CD3 Ϫ/low thymocytes and increased proliferation of SP thymocytes. In this report we extend these findings to show that CD34 ϩ thymocytes express high levels of surface IL-7R beginning at the CD34 high CD5 ϩ CD1a Ϫ stage of maturation and that this subpopulation is responsive to the anti-apoptotic and proliferative effects of IL-7.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Notably, they include early thymocyte progenitors, including CD34 ϩ subpopulations, as well as more mature SP thymocytes. These results confirm previously published data from Okamoto et al (17), who showed that IL-7 treatment of human TOCs led to decreased apoptosis and increased intracellular Bcl-2 levels in immature CD3 Ϫ/low thymocytes and increased proliferation of SP thymocytes. In this report we extend these findings to show that CD34 ϩ thymocytes express high levels of surface IL-7R beginning at the CD34 high CD5 ϩ CD1a Ϫ stage of maturation and that this subpopulation is responsive to the anti-apoptotic and proliferative effects of IL-7.…”
Section: Discussionsupporting
confidence: 82%
“…IL-7-mediated up-regulation of Bcl-2 has been shown to promote the survival of murine and human T cells (5,17,18,40). Because over-expression of Bcl-2 abrogates glucocorticoid-induced apoptosis of murine thymocytes (41), we examined the effects of IL-7 on glucocorticoid (dexamethasone) treatment of human thymocytes.…”
Section: Il-7 Increases Intracellular Bcl-2 Levels and Prevents Dexammentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, IL-7 provides potent antiapoptotic and proliferative signals to early thymocyte progenitors, mainly single positive 152 The contribution of IL-7 to thymic Tcell regeneration has been indicated by experiments using thymic organ culture systems, in which exogenous IL-7: (1) increased the frequency of TRECs in fetal, as well as infant, thymi, indicating that increased rearrangement of a TCRs had occurred; 153 (2) together with SDF-1, it enhanced the viability of CD34 þ T-cell precursors, by modulating the expression of Bcl-2 and Bax, and stimulated their proliferation. 153 In macaques infected with SIV, IL-7 induces both central renewal and a peripheral expansion of T lymphocytes associated with cell activation, without increasing the viral load. 154 However, comparison of pathogenic and nonpathogenic models of SIV infection showed that elevated levels of IL-7 are associated with disease progression.…”
Section: Impairment Of Hiv-specific Cd8 T Cellsmentioning
confidence: 99%
“…Even naïve T cells are, therefore, present in identical replicates generated during and shortly after T-cell development in the thymus or in the periphery. Estimates of clonal sizes have come from the dilution of TRECs during thymic development (Douek et al, 1998;Okamoto et al, 2002). We have used TREC measurements in cord blood of babies born at different gestational ages (Schonland et al, 2003).…”
mentioning
confidence: 99%